Comprehensive Transcriptomic Profiling of Murine Osteoclast Differentiation Reveals Novel Differentially Expressed Genes and LncRNAs - Toor, Salman M.; Wani, Sachin; Albagha, Omar M. E. (Frontiers in Genetics, 2021)
Osteoclasts are the sole bone resorbing cells, which undertake opposing roles to osteoblasts to affect skeletal mass and structure. However, unraveling the comprehensive molecular mechanisms behind osteoclast differentiation is necessitated to overcome limitations and scarcity of available data, particularly in relation with the emerging roles of long non-coding RNAs (LncRNAs) in gene expression. In this study, we performed comprehensive and progressive analyses of the dynamic transcriptomes of murine osteoclasts, generated in vitro. We compared the total RNA-based transcriptomes of murine bone marrow derived cells with differentiated osteoclasts, while focusing on potentially novel genes and LncRNAs to uncover critical genes and their associated pathways, which are differentially regulated during osteoclast differentiation. We found 4,214 differentially regulated genes during osteoclast differentiation, which included various types of LncRNAs. Among the upregulated protein coding genes not previously associated with osteoclast are Pheta1, Hagh, Gfpt1 and Nol4, while downregulated genes included Plau, Ltf, Sell and Zfp831. Notably, we report Nol4 as a novel gene related to osteoclast activity since Nol4 knock out mice Nol4em1(IMPC)J exhibit increased bone mineral density (BMD). Moreover, the differentially expressed LncRNAs included antisense and long intergenic non-coding RNAs, among others. Overall, immune-related and metabolism-related genes were downregulated, while anatomical morphogenesis and remodeling-related genes were upregulated in early-differentiated osteoclasts with sustained downregulation of immune-related genes in mature osteoclasts. The gene signatures and the comprehensive transcriptome of osteoclast differentiation provided herein can serve as an invaluable resource for deciphering gene dysregulation in osteoclast-related pathologic conditions.